USING THE METHODS OF WAVELET ANALYSIS AND SINGULAR SPECTRUM ANALYSIS IN THE STUDY OF RADIO SOURCE BL LAC - Donskykh, G. I.; Ryabov, M. I.; Sukharev, A. I.; Aller, M. (Одеські астрономічні публікації, 2014)
We investigated the monitoring data of extragalactic source BL Lac. This monitoring was held withUniversityofMichigan26-meter radio telescope. To study flux density of extragalactic source BL Lac at frequencies of 14.5, 8 and 4.8 GHz, the wavelet analysis and singular spectrum analysis were used. Calculating the integral wavelet spectra allowed revealing long-term components (~7-8 years) and short-term components (~ 1-4 years) in BL Lac. Studying of VLBI radio maps (by the program Mojave) allowed investigating features of components movement relatively to the VLBI core. The data of radio astronomy observations were also investigated using singular spectrum analysis. This method can solve the task of allocating trend, detection of periodic components and band-pass filtering (reconstruction of time series from quantity of main components, the last corresponds to individual bands of periods on time-frequency spectra or Fourier spectra). Singular spectrum analysis does not use the analyzing function, so its calculations allow to distinguish various components of investigated series with a high accuracy. To get spectral power distribution depending on time in the studied narrowband components obtained by singular spectrum analysis, short-term Fourier transformation was used.